Genomic changes of Lassa virus associated with mammalian host adaptation - Linda Easterbrook; Xiaofeng Dong; Jack Smith; Susan Fotheringham; Sarah Kempster; Catherine Hartley; Tessa Prince; Victoria Graham; Emma Kennedy; Stephen Findlay-Wilson; Lucy Crossley; Roger Hewson; et al. (BMC Genomics)
Abstract Background Lassa virus (LASV) causes a severe haemorrhagic fever in humans, with estimates of 100,000 to 300,000 infections annually in endemic regions and accounting for around 5000 deaths. The natural reservoir is the Mastomys rat, but through zoonotic transmissions humans are accidental hosts. Regular outbreaks continue to exert pressures on public health systems, with its ability to cause nosocomial infections posing risks to healthcare workers. It is a concern that larger outbreaks and introduction of LASV to new territories will intensify, including risk of adaptation to new mammalian host reservoirs. Results To evaluate genetic changes in LASV during adaptation to a new host, a guinea pig model of infection was utilised. Initial infection with LASV stocks cultured from cell culture resulted in only mild or subclinical disease. To study the susceptibility in naïve animals, the virus was serially passaged which increased clinical signs during disease progression ultimately resulting in severe disease. An RNAseq and consensus mapping approach was undertaken to evaluate nucleotide changes in LASV genome from each animal at each passage. Conclusions During adaptation to guinea pigs, no significant new mutations occurred. Instead, a selection pressure on two genes of the L segment was observed resulting in their increased frequency in the genome population during passaging.